As Time Goes By: colonialism, the revision of the past and Brexit. Issue 1 (2nd January 2023) - Stratton, Jon
Abstract: One component in the vote to leave the European Union was a nostalgic image of Empire and the assertion by Brexiteers like Boris Johnson that after Britain had left the EU new trade links would be made with countries who were members of the Commonwealth, countries that Britain had previously governed as colonies. The foundation for this idea was the understanding that Britain's governing of its colonies had been benign and, indeed, that British control had brought with it the benefits of civilisation. This view of the British empire was pervasive in the UK. This article focuses on the sitcom As Time Goes By in which the male protagonist, Lionel, is writing a book about his time in Kenya in the 1950s and 1960s. Everybody who reads the ms considers it boring. Yet Kenya during those decades was subject to a grass-roots uprising against the British colonists known as Mau Mau and Kenya was granted independence in 1963 by which time large numbers of white settlers had left the country. The portrayal of Lionel's book as boring elides this history and reinforces the perception that British colonialism was well received by the indigenous population.